Proceedings of seventh international conference the tawhidi epistemology : zakat and waqf economy, 6-7 January 2010 - International Conference 2010 : Bangi, Selangor).; Abdul Ghafar Ismail; Mohd. Ezani Mat Hassan; Shahida Shahimi; Universiti Kebangsaan Malaysia; Universiti Kebangsaan Malaysia. Institut Islam Hadhari; Malaysia. Jabatan Perdana Menteri; Malaysia. Jabatan Wakaf, Zakat dan Haji.; Malaysia. Jabatan Kemajuan Islam; Institut Latihan Islam Malaysia (Bangi : Institut Islam Hadhari, Universiti Kebangsaan Malaysia, 2010)
Contains working paper presents in seventh international conference on tawhidi epistemology at Bangi.
Title from first screen of PDF.
System requirement: Adobe Acrobat Reader.
Keywords: Zakat; Islam -- Charities; Finance -- Religious aspects -- Islam